2012
DOI: 10.1155/2012/570948
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Ginger Ameliorates Fructose-Induced Fatty Liver and Hypertriglyceridemia in Rats: Modulation of the Hepatic Carbohydrate Response Element-Binding Protein-Mediated Pathway

Abstract: Ginger has been demonstrated to improve lipid derangements. However, its underlying triglyceride-lowering mechanisms remain unclear. Fructose overconsumption is associated with increase in hepatic de novo lipogenesis, thereby resulting in lipid derangements. Here we found that coadministration of the alcoholic extract of ginger (50 mg/kg/day, oral gavage, once daily) over 5 weeks reversed liquid fructose-induced increase in plasma triglyceride and glucose concentrations and hepatic triglyceride content in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 50 publications
5
62
1
2
Order By: Relevance
“…Fructose consumption may induce excessive lipid accumulation in liver [27]. We have recently demonstrated that treatment with the ethanolic extract of ginger attenuates fructose-induced fatty liver in rats [24]. In the present study, however, five-week fructose feeding did not alter renal accumulation of triglyceride and total cholesterol in rats.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Fructose consumption may induce excessive lipid accumulation in liver [27]. We have recently demonstrated that treatment with the ethanolic extract of ginger attenuates fructose-induced fatty liver in rats [24]. In the present study, however, five-week fructose feeding did not alter renal accumulation of triglyceride and total cholesterol in rats.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, fructose in drinking water was used in the present study, in accordance to this rationale and the previous research protocol [24,25,28,29]. …”
Section: Methodsmentioning
confidence: 99%
“…Similar effect was observed by Al-Hoory et al, [36] who reported a reduction in serum triglyceride in alloxan-induced diabetic rats after 4 weeks of raw ginger extract administration at a dosage of 500mg/kg body weight. On the other hand the significant increase in serum triglyceride by cooked ginger extract corroborates the report of Gao et al, [38] who observed an increase in plasma triglyceride in fructose-induced hypertriglyceridemic rats by 5 weeks oral administration of alcoholic ginger extract at 50mg/kg body weight.…”
Section: Serum Triglyceridessupporting
confidence: 90%
“…Real-time PCR was performed as described previously [21, 22]. Total RNA was isolated from livers of individual rats using TRIzol (Takara, Dalian, China).…”
Section: Methodsmentioning
confidence: 99%